Handbook of child and adolescent aggression - Malti, Tina; Rubin, Kenneth H.; Vaillancourt, Tracy (New York : The Guilford Press, 2018)
"Presenting cutting-edge work from leading scholars, this authoritative handbook reviews the breadth of current knowledge on aggression from infancy through adolescence. The volume explores the forms and functions of aggression and the multiple factors that contribute to its emergence, development, and consequences, including genetic and biological influences, temperament, family dynamics, peer relations, and social inequality. It provides up-to-date perspectives on problems such as disruptive and defiant behaviors, bullying (including cyberbullying), social aggression, and youth violence, and examines relations between aggression and normative social-emotional and social-cognitive development. Identifying important implications for practice and policy, contributors describe effective approaches to screening, assessment, intervention, and prevention in family, school, community, and clinical settings."--
"Aggressive behavior during childhood and adolescence is an important risk factor for later serious and persistent adjustment problems in adulthood, including criminal behavior, school dropout as well as family-related and economic problems. Researchers have thus deployed considerable efforts to uncover what drives individuals to attack and hurt others. Each chapter explores the issue of aggression with an introduction, theoretical considerations, measures and methods, research findings, implications, and future directions"--
Foundations of Aggression, Trajectories, and Antecedents. Aggression in Childhood and Adolescence: Definition, History, and Theory -- Clinical Classifications of Aggression in Childhood and Adolescence -- Developmental Trajectories of Aggression Subtypes: From Early to Late Childhood -- Behavior Genetics of Aggression -- Psychophysiology of Aggression -- Temperament and Aggression -- Social-Emotional Development and Aggression -- . Social-Cognitive Development and Aggression -- Aggression in Context. Parenting, Parent-Child Relationships, and the Development of Aggression during Childhood and Adolescence -- Aggression and Functioning with Peers -- Aggression and Morality in Childhood and Adolescence -- Social Networks and Aggression -- Cyberbullying -- Poverty, Social Inequality, and Aggression -- Interventions and Policy Implications. Measuring Social-Emotional Correlates of Aggression in Children and Adolescents -- Youth-Focused Intervention for Severe Aggression -- Family-Based Treatments for Aggressive Problem Behavior -- Preventing Aggression and Youth Violence in Schools -- International Perspectives on Bullying Prevention -- Can Positive Youth Development Programs Prevent Youth Violence?: The Role of Regulation of Action and Positive Social Engagement -- CHAPTER 21. Challenges and Priorities for Researchers -- Challenges and Priorities for Practitioners and Policymakers
Includes bibliographical references and indexes.
Description based on online resource; title from digital title page (viewed on May 30, 2023).
eBooks on EBSCOhost
Keywords: Aggressiveness in children; Aggressiveness in adolescence; Developmental psychology; Agressivité chez l'enfant.; Agressivité chez l'adolescent.; Psychologie du développement.; PSYCHOLOGY -- Developmental -- Child; MEDICAL -- Psychiatry -- Child & Adolescent; FAMILY & RELATIONSHIPS -- Life Stages -- General; PSYCHOLOGY -- Developmental -- General; PSYCHOLOGY -- Developmental -- Lifespan Development; PSYCHOLOGY -- General; Aggressiveness in adolescence; Aggressiveness in children; Developmental psychology